Peer-based recovery strategy for reliable multicast transport protocol (RMTP) - Lu, Clariza M. (2005)
"Multicasting provides an efficient way of delivering data from a sender to a group of receivers. This technology has become very prevalent because of the increasing demand for distributed applications such as video conferencing, which requires real-time delivery of data, and distributed interactive simulations which involves total reliability of data sent. An existing framework for reliable multicasting called the Reliable Multicast Transport Protocol (RMTP) was the first to use hierarchical arrangement of hosts to achieve scalability. The protocol implements a server-based recovery scheme, where a host (or server) called the Designated Receiver or DR is chosen to be responsible for detecting recovery requests and recovering the lost packet for each partition or local group. Although RMTP provides a useful multicast transport service, additional work can be done to further minimize end-to-end delay. Since the prootocol bounds the transmission speed to the slowest receiver, it is important to have an efficient recovery mechanism. This thesis presents a reliable multicast protocol based on RMTP called peer-based RMTP (PB-RMTP). The new protocol makes use of special peer receivers within a local group to help the DRs minimize delay by sending retransmissions for lost packets. Experiments showed that PB-RMTP improved end-to-end latency and reduced retransmissions for lost packets compared with the original RMTP. A Java-based network simulation tool that supports multicast routing called Java Network Simulator (JNS) was used in the experiments. New modules were deployed in JNS to support RMTP and PB-RMTP to simulate the revisions in the recovery system."